Kepailitan Badan Hukum BUM Desa dalam Peraturan Perundang-Undangan di Indonesia - Ridlwan, M Pasca Zakky Muhajir (Maliyah : Jurnal Hukum Bisnis Islam, 2022)
The Village Autonomy Provides the widest possible authority to the village to explore and manage the economic potensial of the village, including by forming village owned enterprises (BUM Desa). After the issuance of government Regulation of Law No. 2 of 2022 concerning job creation which recently Received validation as a law, there has been a charge in the institutional aspect of village Owned Enterprises (BUM Desa). BUM Desa, which previously only existed as a business entity, has now transformed into a legal entity. The legal entity form of BUM Desa is different from other legal entity forms in Indonesia, such as Limited Liability Company, State-Owned Enterpries, and Cooperatives. The Transformation from a more business entity to a legal entity has legal implications not only institutionally, but also in term of legal relationships with other parties. As s legal entity, BUM Desa is also granted authority to establish legal entity based business units. These legal implications may lead to bankruptcy Of BUM Desa if not managed properly. However, there is currently no adequate legal framework that regulates in detail the mechanism for filing bankruptcy petition to the commercial court to declare BUM Desa Bankrupt, and the legal consequences of BUM Desa being declared bankrupt, including related to its assets, wealth, and organizational structure. This research uses a doctrinal and theoretical legal research method with an approach to legislation and conceptual concepts. The Conclusion of this research is that more detailed regulations are needed regarding the legal entity form of BUM Desa, especially concerning bankruptcy of BUM Desa.